Impact of Zirconia Crowns and the Vertiprep Technique on Periodontal Tissues in Patients with Periodontitis - Tonklevskyi, Р. Г. (Actual Dentistry, 2025)
Actuality. The article focuses on examining the impact of zirconium crowns on gums in periodontitis, as well as evaluating the Vertiprep technique as a tool for enhancing treatment outcomes. The use of zirconium crowns in dental practice has increased significantly due to their positive properties, such as high biocompatibility, aesthetic qualities, and strength. However, the effects of these crowns on periodontal tissues in the presence of diseases such as periodontitis still require detailed analysis. Periodontitis is a chronic inflammatory disease that affects the tissues supporting the teeth and can lead to tooth loss. Therefore, it is essential to consider not only the aesthetic and mechanical characteristics of the materials but also their impact on the surrounding tissues, particularly the gums. The article also focuses on the Vertiprep technique, which represents an innovative approach to preserving periodontal tissues and enhancing their functional properties, a crucial aspect for patients with periodontitis. This method enables achieving high results in maintaining the health of the soft tissues in the gums, which, when combined with the correct selection of crown material, can significantly enhance the treatment outcomes. The article presents data from clinical studies confirming the effectiveness of zirconium crowns in treating patients with periodontitis, as well as the results of using the Vertiprep technique in combination with these crowns. The possible risks and side effects associated with the use of zirconium crowns in patients with periodontal diseases are also considered, which enables the assessment of their feasibility in clinical practice. This work aims to review current data on the impact of tooth preparation techniques (Vertiprep vs. step-down) and materials for orthodontic structures (zirconia vs. metal-ceramic) on the condition of periodontal tissues in patients with periodontitis. Materials and methods. This study is a review of the current literature, conducted by analyzing publications from international databases (PubMed, Scopus, and Web of Science) over the past decade. The primary focus is on clinical trials, systematic reviews, and prospective studies that compare the effectiveness of zirconia and metal-ceramic crowns, as well as the Vertiprep preparation technique and traditional pretreatment. The assessment of effectiveness was based on indicators such as plaque index (PI), periodontal pocket depth (PPD), bleeding index (BI), gingival recession, and marginal periodontal stability.